Overview of systematic reviews of probiotics in the prevention and treatment of antibiotic-associated diarrhea in children - Yang, Qingrui; Hu, Zeyu; Lei, Yuyu; Li, Xinzhu; Xu, Chao; Zhang, Jie; Liu, Haitao; Du, Xiaoquan (Frontiers in Pharmacology, 2023)
Background: Antibiotics alter the microbial balance commonly resulting in antibiotic-associated diarrhea (AAD). Probiotics may prevent and treat AAD by providing the gut barrier and restoring the gut microflora. This study will overview the Systematic Reviews (SRs) of probiotics in preventing and treating AAD in children. It will also assess the reporting, methodological, and evidence quality of the included SRs to provide evidence for their clinical practice. Methods: After searching PubMed, Embase, Cochrane Library, CNKI, CBM, VIP, and WanFang Data databases, and finally included SRs of probiotics in the prevention and treatment of AAD in children, which were published before October 1, 2022. The reporting, methodological, and evidence quality of the included SRs were assessed by PRISMA 2020 statement, AMSTAR 2 tool, and GRADE system. Results: A total of 20 SRs were included, and the results of PRISMA 2020 showed that 4 out of 20 SRs with relatively complete reporting, and the others within some reporting deficiencies, with scores ranging from 17 points to 26.5 points; the results of AMSTAR 2 showed that 3 SRs belonged to moderate quality level, 10 SRs belonged to low-quality level and 7 SRs being extremely low-quality level; the results of the GRADE system showed that a total of 47 outcomes were reported for the included SRs, three were high-level evidence quality, 16 were medium-level evidence quality, 24 were low-level evidence quality, and four were extremely low-level evidence quality; the results of the Meta-analysis showed that high doses (5 to 40 billion CFUs per day) of probiotics had a significant effect in the prevention of AAD, but it is too early to conclude the effectiveness and safety of other probiotic drugs for AAD in children, except for Lacticaseibacillus rhamnosus and Saccharomyces boulardii. Conclusions: Current evidence shows that probiotics effectively prevent and treat AAD in children, and the effect of probiotics on pediatric AAD may be a potential dose-response effect. However, the conclusion should be treated with caution due to deficiencies in the methodological, reporting, and evidence quality of the included SRs. Therefore, the methodological, reporting, and evidence quality of relevant SRs still need further improvement.